1999
DOI: 10.1152/ajpheart.1999.276.1.h53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin-converting enzyme inhibition on protein kinase C and SR proteins in heart failure

Abstract: We tested the hypothesis that activation of protein kinase C (PKC) isoforms in pressure-overload heart failure was prevented by angiotensin-converting enzyme (ACE) inhibition, resulting in normalization of cardiac sarcoplasmic reticulum (SR) Ca2+ATPase (SERCA) 2a and phospholamban protein levels and improvement in intracellular Ca2+ handling. Aortic-banded and control guinea pigs were given ramipril (5 mg ⋅ kg−1 ⋅ day−1) or placebo for 8 wk. Ramipril-treated banded animals had lower left ventricular (LV) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 36 publications
1
56
0
2
Order By: Relevance
“…9,10,24 Equal amounts of membranous and cytosolic protein were subjected to electrophoresis, and the subcellular localization of PKC isoforms was examined by quantitative immunoblotting with isoform-specific antibodies as reported previously. 9,10,24 Membrane/cytosol ratios of immunoreactivity were used as indices for the extent of translocation of PKC isoforms. 9,10,24…”
Section: Protein Extraction and Separation Of Membranous And Cytosolimentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,24 Equal amounts of membranous and cytosolic protein were subjected to electrophoresis, and the subcellular localization of PKC isoforms was examined by quantitative immunoblotting with isoform-specific antibodies as reported previously. 9,10,24 Membrane/cytosol ratios of immunoreactivity were used as indices for the extent of translocation of PKC isoforms. 9,10,24…”
Section: Protein Extraction and Separation Of Membranous And Cytosolimentioning
confidence: 99%
“…4 In animal models of cardiac hypertrophy and heart failure by pressure overload, translocation and activation of PKC-␣ and PKC-⑀ isoforms are observed. 9,24 We have demonstrated that transgenic overexpression of a constitutively active mutant of the PKC-⑀ isoform in the mouse heart results in concentric cardiac hypertrophy. 11 Conversely, overexpression of PKC-␤2 in transgenic mouse heart causes a dilated cardiomyopathy phenotype.…”
Section: Critical Role Of the Dag-pkc Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…ACEI and Ang II receptor antagonists have been reported to prevent translocation of ⑀PKC in the heart, 29,30 and in a recent study from our laboratory, ⑀PKC was shown to mediate Ang II-mediated inhibition of pump activity. 31 Aldosterone-induced activation of PKC in noncardiac tissue has been reported by several studies, 32,33 and a similar response in the heart might contribute in part to the aldosterone-induced inhibition of pump function observed in the present study.…”
Section: Mechanism For Additive Effect Of Aldosterone Antagonistsmentioning
confidence: 91%
“…20,31 Such a change has been demonstrated in aortic-banded guinea pigs, as they develop pressure-overloaded heart failure, and the decrease in Ca 2+ -ATPase expression can be attenuated significantly by 8 weeks of treatment with an ACE inhibitor. 32 Neuroendocrine activity has also been implicated, in particular local production of angiotensin II, in the apoptosis hypothesis for explaining progressive alterations in chamber contractility. Myocyte apoptosis has been demonstrated to contribute in rats and mice to the transition from hypertrophy to early heart failure.…”
Section: Transition To Heart Failurementioning
confidence: 99%